City Avoidance in the Early Phase of Psychosis: A Neglected Domain of Assessment and a Potential Target for Recovery Strategies - Conus, Philippe; Abrahamyan Empson, Lilith; Codeluppi, Zoé; Baumann, Philipp Sebastien; Söderström, Ola; Söderström, Dag; Golay, Philippe (Frontiers in Psychiatry, 2019)
Background: A considerable amount of research has explored the link between living in an urban environment during childhood and the increased the risk to develop psychosis. However, the urban milieu is more than a risk factor as it is also a place for socialization and enrichment. The aims of the current study were to explore, in a large sample of early psychosis (EP) patients, their pattern of use of the city, their perception when exposed to various critical stressors and their sensitivity to diverse forms of stimuli. Methods: We sent a questionnaire (based on previous work conducted in a group of patients, including video-recorded walk-along in the city and a literature review) to 305 EP patients and to 220 medical students. Results: Response rate in patients was low (38%). City avoidance and negative perceptions towards the urban environment increased in patients after onset of psychosis. Patients’ tendency to avoid city center correlates with both problematic social interactions and stimuli perceived as unpleasant. Patients seemed less likely to enjoy urban spaces considered as relaxing, suggesting a lower capacity to benefit from positive aspects of this environment. Conclusions: The development of psychosis influences the way EP patients perceive the city and their capacity to feel at ease in the urban environment, leading to a high rate of city avoidance. Considering the possible influence of city avoidance on social relations and the recovery process, the development of strategies to help patients in this regard may have a significant effect on their recovery process.